EFEK MODEL PROBLEM BASED LEARNING (PBL) DAN KONVENSIONAL TERHADAP HASIL BELAJAR SISWA FISIKA - Ahmad Fauzi Pohan (Sekolah Tinggi Teknologi Industri Padang, 2016)
This aim of this study to determine the effects of problem based learning to learning outcomes. This research sample was taken two classes with simple random sampling that are IX-3 and IX-2 to experiment groupand control group are 35 students respectively. The average scores result pretest both of treatment group and control group, was 35.29 and 34.86. The average scores result post-test both of the treatment group and control group, was 60.43 and 54.43. The scores pre and post-test mentioned T-test two parties, and the result of the detached score of pre-test obtained tcount< ttable, that the initial ability of students both of groups are same, while the T-test results for score post-test obtained tcount> ttable, that there is a difference in student learning outcomes with applying problem based learning with conventional learning models. Keywords: Problem Based Learning, Conventional, Simple Random Sampling.